Case report: Recurrence of hypertension after renal artery angioplasty due to the progression of focal renal fibromuscular dysplasia - Hong, Mona; Kang, Yuanyuan; Xu, Jianzhong; Wang, Jiguang (Frontiers in Cardiovascular Medicine, 2022)
Whether fibromuscular dysplasia (FMD) is a progressive disease, remains unclear. We reported a case of focal renal artery FMD that slowly progressed to a branching artery over a few years after the angioplasty without in-stent restenosis, which reconfirms that focal FMD is progressive and that such progression may be segmental. Stenting may be an option for young, risk factor-free patients with focal FMD.